Synthesis and Characterisation of Alginate-Based Capsules Containing Waste Cooking Oil for Asphalt Self-Healing - Jose Norambuena-Contreras (Applied Sciences, 2022)
This paper presents the synthesis and characterisation of biopolymeric capsules for asphalt self-healing. A sodium alginate biopolymer extracted from the cell wall of brown algae was used as the encapsulating material to contain Waste Cooking Oil (WCO) as a potential encapsulated rejuvenating agent for aged bitumen. Polynuclear capsules were synthesised by ionic gelation. The size, surface aspect and internal structure of the WCO capsules were evaluated using Optical and Scanning Electron Microscopy. The physical-chemical properties and thermal stability of the WCO capsules and their components were also evaluated. Moreover, the diffusion process and self-healing capability of the released WCO on cracked bitumen test samples were determined by image analysis through fluorescence microscopy. The main results of this study showed that the WCO capsules presented a suitable morphology to be mixed in asphalt mixtures. WCO capsules and their components presented mechanical and thermal stability and physical-chemical properties which suggest their feasibility for self-healing applications. It was proven that the encapsulated WCO can diffuse in the aged bitumen, reducing its viscosity and promoting the self-healing of microcracks.